FORMULASI SEDIAAN PASTA GIGI BUBUK RIMPANG JAHE PUTIH (Zingiber officinale Rosc) ASAL DAERAHNAMROLE KABUPATEN BURU SELATAN DENGAN VARIASI KONSENTRASI BAHAN PENGIKAT - Micie Sariwating; Cut Bidara Panita Umar; Nurliani Tomia (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
The rhizome of white ginger (Zingiber officinale Rosc) has been known by the public because apart from being a cooking spice, it can also be used as medicine, one of which is to treat toothache. Control of dental and oral health problems is to use toothpaste properly and regularly. The higher the concentration of the binder (sodium CMC), the more compact the toothpaste preparation will be and the release of the active substance is less than optimal, besides that it will be difficult to apply at the time of use. On the other hand, the concentration of the binder is too low, causing the preparation to be easily crushed and disintegrate like a lotion. Variations in the concentration of different binders were made to see the physical form among the three formulations of toothpaste which had the best consistency and met the requirements. The purpose of this study was to identify the chemical content of white ginger (Zingiber officinale Rosc) rhizome, to formulate white ginger (Zingiber officinale Rosc) powder toothpaste with various concentrations of binders and to evaluate the preparation of white ginger (Zingiber officinale Rosc) powdered toothpaste. This research was conducted using laboratory experimental methods. The result of this research is that white ginger (Zingiber officinale Rosc) rhizome powder contains alkaloids, flavonoids, tannins and triterpenoids. White ginger rhizome powder (Zingiber officinale Rosc) can be formulated into toothpaste preparations. The toothpaste with the most physically stable consistency and fulfills the requirements is formula III (4% CMC sodium)